Karakteristik Permen Gummi dari Lidah Buaya (Aloe Vera L.) dan Ekstrak Bunga Rosella (Hibiscus Sabdariffa L.) - Sandi, Alya Nurulita; Pratiwi, I Desak Putu Kartika; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPA, 2024)
Gummy candy is a soft candy made from water or fruit juice, a mixture of sugar, and gelling ingredients. Aloe vera juice is one of the ingredients that can be made into gummy candy. The use of rosella flowers as a natural coloring is expected to increase the color attractiveness, vitamin C and antioxidant activity of gummy candy. This study aims to determine the effect of the comparison of aloe vera and rosella flower on the characteristics of gummy candy and to obtain the right comparison to produce gummy candy with the best characteristics. This study used a completely randomized design with treatment ratios of aloe vera and rosella flower, namely 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50. Parameters observed in this study included water content, vitamin C, total anthocyanins, antioxidant activity, and sensory evaluation. The data obtained was analyzed using variance and if it had an effect on the parameters, Duncan's Multiple Range Test was carried out. The results showed that the comparison of aloe vera and rosella flower had a significant effect (P<0.05) on water content, vitamin C, total anthocyanin, antioxidant activity, and sensory color, aroma, texture, taste, and overall acceptability. The best treatment was obtained in a ratio of 70 percent aloe vera and 30 percent rosella flower with a water content of 18.57 percent, vitamin C 162.61 mg/100g, total anthocyanin 0.18 mg/100g, antioxidant activity 23.26 percent, with color reddish brown was liked, aroma and chewy texture were slightly liked, taste and overall acceptance were liked by the panelists. Keywords : aloe vera, gummy candy, rosella flower extract